Mapping 50 years of sport psychology-performance meta-analyses: a PRISMA-ScR scoping review - Lochbaum, M.; Lane, A. M. (Sports, 2025)
Sport psychology has generated an expansive body of literature on how psychological factors influence athletic performance, yet no review has systematically mapped this body of research. Guided by the PRISMA-ScR framework, this study charted published meta-analyses that investigated links between psychological constructs and sport performance. After conducting comprehensive searches, we identified 137 relevant papers, of which 73 met our inclusion criteria for athlete samples and performance outcomes. The included meta-analyses, published between 1988 and 2025, represented authors from at least 30 countries and covered more than 40 different constructs. Mental practice, confidence, achievement goals, anxiety, cohesion, mindfulness, and neurofeedback were the most frequently studied topics. Publication activity has accelerated rapidly since 2020, reflecting the maturation and diversification of evidence synthesis in sport psychology. Rather than aggregating effect sizes, this review maps methodological trends, recurring themes, and areas of limited coverage. The resulting catalog highlights where the evidence base is strongest, identifies emerging opportunities, and provides a foundation for future quantitative reviews to progress consensus development.